Development of ICT (Information And Communication Technology) Media of The Bamboozle Type Using The Discovery Learning Model in Indonesian Language Learning at Madrasah Ibtidaiyah - Muhammad Majdi; Nur Faizatina (The International Journal of Education Management and Sociology, 2025)
This study aims to describe the implementation of Information and Communication Technology (ICT)-based learning media, specifically the Bamboozle platform, in Indonesian language learning for fifth-grade elementary school students on the topic of intrinsic elements of a story. Bamboozle is an online educational game-based learning media that does not require students to create accounts or use special devices, making it highly suitable for collaborative and interactive learning contexts. This research employs a descriptive qualitative approach, utilizing observation, interviews, and documentation as data collection methods. Using a qualitative approach, the study involves Madrasah Ibtidaiyah (MI) students as subjects to explore their learning experiences when using Bamboozle integrated with the Discovery Learning model. The results indicate that the use of Bamboozle positively impacts student engagement during the learning process, particularly in aspects of communication, collaboration, and fostering a healthy competitive spirit. This media facilitates the understanding of abstract concepts and increases students' learning motivation through a fun and participatory classroom environment. One of Bamboozle's main advantages is its ability to promote teamwork without the need for complex technological infrastructure. Nevertheless, the study also identifies several challenges, such as the limitation on the number of characters allowed in question creation and the absence of an individual assessment system. These issues present obstacles in objectively evaluating each student’s learning achievements.